ANALISIS MINAT MASYARAKAT MENABUNG DIBANK SYARIAH (Studi Kasus di Kampung Paya Bedi Aceh Tamiang) - febi febi; Ainun Mardiah; Agung Pradhana Putra; Junaidi Junaidi (JIM: Jurnal Ilmiah Mahasiswa, 2019)
This study aims to determine the factors that influence interest in saving the village community Paya Bedi in Bank Syariah Kota Kualasimpang and to know the influence partially and simultaneously to the interest of saving society. There are several factors that influence the society in doing saving include the influence of service factors and product factors. This research is quantitative, using 100 respondents as research sample. Sampling in this research is done by Random sampling method, that is the technique of determining the selected sample regardless of the level that exist in that population. Data collection techniques were conducted using questionnaires as many as 15 items of questions assessed by Likert scale 1-5 and tested its feasibility using the validity and realiability test. The collected data was done by classic assumption test including multicolinearity test, heterokedastisitas, normality and linearity then analyzed using multiple regression analysis with determination test method, F test and t test. Based on multiple regression analysis at significance level 5% showed that simultaneously service factor and product factor have positive significant effect to decision of interest of saving society. The result of the research also shows partially that (1) there is a significant positive effect of service factor on the interest of saving the society of Kampung Paya Bedi in Bank Syariah Kota Kualasimpang; (2) there is no significant effect of the product factors on the interest of saving the people of KampungPayaBedi in Bank Syariah Kota Kualasimpang.